Deploying multiple sensor applications in a network - Kondam, Sudhir Chander Reddy (Kansas State University, 2010)
TinyOS is an open-source component based operating system designed for highly memory constrained wireless embedded sensor network. TinyOS includes interfaces and components for communication management, routing and data acquisition tools to be refined further for custom applications. This project aims at developing a system which detects overlapping paths for data collection in different applications in the network and utilizing that information for efficient data acquisition. This prevents a reconfiguring the entire network of wireless sensor nodes (called motes) for each new application request. The application for initial or first data acquisition request tries to build the tree architecture on motes in the network where each node in the tree knows its immediate parent and children. The application builds the tree routed at the base station for the initial request and each intermediate node sends data to its parent when the data request is made. Each base station can request Light, Temperature and Passive Infrared sensory data from all or a subset of motes present in the system. When a new base station comes and connects to the network through a mote/node in the tree, the system reconfigures only those parts of the tree built in the initial phase which do not overlap with the tree required for the new base station as the root, all the other overlapping parts of the tree are left unchanged. We present experimental result to illustrate the efficiency of the approach.
Keywords: Wireless Sensor Network; Sensor Network; Motes; TinyOS; Base-station; message; Computer Science (0984)